2017
DOI: 10.1017/jfm.2017.166
|View full text |Cite
|
Sign up to set email alerts
|

Streaming patterns in Faraday waves

Abstract: Waves patterns in the Faraday instability have been studied for decades. Besides the rich dynamics that can be observed on the waves at the interface, Faraday waves hide beneath them an elusive range of flow patterns -or streaming patterns-which have not been studied in detail until now. The streaming patterns are responsible for a net circulation in the flow which are reminiscent of convection cells. In this article, we analyse these streaming flows by conducting experiments in a Faraday-wave setup. To visual… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
41
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 34 publications
8
41
0
2
Order By: Relevance
“…The relation between the experiment quantities and the dimensionless parameters ν, µ, γ, as well as the envelope ψ and the time, are given in detail in Refs. [27,36,37]. For our experiments, it can be shown that |ψ| 2 ∼ 10 −3 , µ ∼ 10 −2 , ν ∼ 10 −1 and γ ∼ 10 −1 .…”
Section: Theoretical Description Of Localized Faraday Wavessupporting
confidence: 51%
“…The relation between the experiment quantities and the dimensionless parameters ν, µ, γ, as well as the envelope ψ and the time, are given in detail in Refs. [27,36,37]. For our experiments, it can be shown that |ψ| 2 ∼ 10 −3 , µ ∼ 10 −2 , ν ∼ 10 −1 and γ ∼ 10 −1 .…”
Section: Theoretical Description Of Localized Faraday Wavessupporting
confidence: 51%
“…The case of Faraday waves in a rectangular container was considered in Ref. [39], where no specific surfactant was added. In this study, surface contamination was seemingly present due to the use of tap water, which is easily contaminated.…”
Section: Introductionmentioning
confidence: 99%
“…Nontrivial surface flows in orbital shaking strikingly illustrates the critical influence of surface contamination in wave-induced flow generation [9][10][11][12][13]. We show here that the reversal in the floating raft rotation results from a complex interplay between transport by the rotating sloshing wave, friction with the container wall, and internal stress in the viscoelastic raft [14].…”
mentioning
confidence: 70%
“…We measure the mean motion of the surface covering averaged over the wave period with a camera located above the cylinder. In order to filter out the large-amplitude wave motion and measure only the second order mean flow, the image acquisition is synchronized with the forcing [4,12]. This stroboscopic measurement is sensitive to the total (Lagrangian) mass transport, which includes the (Eulerian) steady streaming contribution and the Stokes drift contribution.…”
mentioning
confidence: 99%